2018
DOI: 10.1111/nph.15007
|View full text |Cite
|
Sign up to set email alerts
|

YODA MAP3K kinase regulates plant immune responses conferring broad‐spectrum disease resistance

Abstract: Mitogen-activated protein kinases (MAPKs) cascades play essential roles in plants by transducing developmental cues and environmental signals into cellular responses. Among the latter are microbe-associated molecular patterns perceived by pattern recognition receptors (PRRs), which trigger immunity. We found that YODA (YDA) - a MAPK kinase kinase regulating several Arabidopsis developmental processes, like stomatal patterning - also modulates immune responses. Resistance to pathogens is compromised in yda alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 83 publications
3
58
0
19
Order By: Relevance
“…Consistent with enhanced flg22‐induced MAPK activation in YDA silencing lines, a partial loss‐of‐function mutant of YDA was recently reported to display slightly delayed but enhanced activation of MAPKs upon flg22 treatment . In the same study, a ΔN‐YDA line generated by crossing the ΔN‐YDA transgene in the L er background to Col‐0 background was also tested for flg22‐induced MAPK activation and resistance to pathogens.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with enhanced flg22‐induced MAPK activation in YDA silencing lines, a partial loss‐of‐function mutant of YDA was recently reported to display slightly delayed but enhanced activation of MAPKs upon flg22 treatment . In the same study, a ΔN‐YDA line generated by crossing the ΔN‐YDA transgene in the L er background to Col‐0 background was also tested for flg22‐induced MAPK activation and resistance to pathogens.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, a kinase dead MAPKKK3 mutant does not affect the interaction between YDA and MKK5, suggesting that the kinase activities of YDA and MAPKKK3/MAPKKK5 are important for the competition for downstream MKKs. Consistent with enhanced flg22-induced MAPK activation in YDA silencing lines, a partial loss-of-function mutant of YDA was recently reported to display slightly delayed but enhanced activation of MAPKs upon flg22 treatment [36]. In the same study, a DN-YDA line generated by crossing the DN-YDA transgene in the Ler background to Col-0 background was also tested for flg22induced MAPK activation and resistance to pathogens.…”
Section: Discussionmentioning
confidence: 77%
“…Remarkably, it was recently found that BAK1 and ER interact, and that they cooperate with other members of the ER pathway [ER‐like1 (ERL1) and ERL2, and the TOO MANY MOUTHS (TMM) RLP] in the regulation of innate immune response (Meng et al ., ; Jordá et al., 2016). Moreover, the YODA MAP3K functioning downstream of the ER–ERLs–TMM–BAK1 complex in the regulation of developmental processes like stomata patterning has also been found to be required for Arabidopsis broad‐spectrum disease resistance (Sopeña‐Torres et al ., ). Remarkably, yda11 and er‐105 mutants show similar cell wall modifications compared with wild‐type plants, as revealed by glycomics profiling (Sopeña‐Torres et al ., ).…”
Section: Molecular Mechanisms For the Perception Of Cwi Alterations Amentioning
confidence: 97%
“…Moreover, the YODA MAP3K functioning downstream of the ER–ERLs–TMM–BAK1 complex in the regulation of developmental processes like stomata patterning has also been found to be required for Arabidopsis broad‐spectrum disease resistance (Sopeña‐Torres et al ., ). Remarkably, yda11 and er‐105 mutants show similar cell wall modifications compared with wild‐type plants, as revealed by glycomics profiling (Sopeña‐Torres et al ., ). The over‐expression of a constitutively activated YODA protein ( CA‐YDA plants) results in broad‐spectrum disease resistance that is independent of canonical immune pathways (e.g.…”
Section: Molecular Mechanisms For the Perception Of Cwi Alterations Amentioning
confidence: 97%
See 1 more Smart Citation